The Effect of Sterilization on Vitamin D Levels in Male and Female Rats - Pratiwi, Hamria; Idris, Irfan; Sari, Dwi Kesuma (Hasanuddin University, 2022)
Sterilization is an operation that can prevent reproduction and is useful as a treatment. Sterilization is done by removing the reproductive organs, in males it is called orchiectomy and in females it is called ovariohysterectomy which causes a decrease in the production of reproductive hormones. Previous studies have proven a physiologic relationship between reproductive hormones and vitamin D activation, but there is no information on the effect of sterilization on vitamin D levels. This study aimed to determine the effect of sterilization on vitamin D levels. This study was experimental with a Posttest-Only Control Group design. design. A total of 24 wistar rats consisting of 12 male rats and 12 female rats and each were divided into two groups, 6 female rats sterilized (ovariohysterectomy), 6 female rats non-sterilized, 6 male rats sterilized (orchiectomy) and 6 male rats non-sterilized. -sterilization. Wistar rats that were 10 weeks old were transferred to their respective cages and given regular feed to all groups of rats for 7 days as an adaptation process, after which sterilization was carried out in the sterilization group. After 6 weeks post-treatment, the rats were 17 weeks old and then blood was taken for examination of Vitamin D levels using the elisa method which was carried out at Hum-Rc Hasanuddin University Hospital. The results showed that the mean value of vitamin D levels in the ovariohysterectomy group was lower than in the non-sterilized group and was significant (Mann-Withney, p<0.05). The orchiectomy group was also lower than in the non-sterlized group and not significant (Independent T test, p> 0.05). It can be concluded that sterilization can reduce vitamin D levels in pets. Keywords: Sterilization, Ovariohysterectomy, Orchiectomy, and Vitamin D